If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -12 = -7x + 10 Reorder the terms: -12 + 4x = -7x + 10 Reorder the terms: -12 + 4x = 10 + -7x Solving -12 + 4x = 10 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. -12 + 4x + 7x = 10 + -7x + 7x Combine like terms: 4x + 7x = 11x -12 + 11x = 10 + -7x + 7x Combine like terms: -7x + 7x = 0 -12 + 11x = 10 + 0 -12 + 11x = 10 Add '12' to each side of the equation. -12 + 12 + 11x = 10 + 12 Combine like terms: -12 + 12 = 0 0 + 11x = 10 + 12 11x = 10 + 12 Combine like terms: 10 + 12 = 22 11x = 22 Divide each side by '11'. x = 2 Simplifying x = 2
| 5x-x=3x-2 | | -x+3=23 | | -2x-6=16 | | x^3-12= | | 7x-(3x+6)=5x-47 | | 5x^2+1=2x | | 2y^3-7y^2+3=0 | | 50x^2+1=2x | | 6x-7x-5=0 | | 16x-282=6x-12 | | 52-6x=12x+18 | | 9x-(7x+2)=3x-22 | | 6x+22=16x-98 | | 3x^2+2x-40=0 | | 3x^2+58x-40=0 | | 3x^2+119x-40=0 | | x^2+25x-24=0 | | 2x+125=6x+93 | | (x)(x+1)(x+2)=720 | | 2x+25=6x+93 | | 3x^2-29x-10=0 | | x^4-4x^2+12x+9= | | x^4-4x^2+12x+9=0 | | 3x+2.3=5x+1.7 | | (3x-2)(x^2-6x+1)=0 | | a*12=b | | 5x+15=70 | | 4x^2-300=0 | | X+y=3x-5 | | 8x-7=7x-5 | | 8x=16.8 | | 7x=24.5 |